FAKTOR-FAKTOR YANG MEMENGARUHI TERJADINYA INSOMNIA PADA LANSIA DI SAMANHUDI KELURAHAN ESTATE KECAMATAN BINJAI SELATAN TAHUN 2016 - Hasan Basri Nasution (Jurnal Riset Hesti Medan, 2016)
Aging is normal, with physical changes and predictable behavior that occurs in all people when they reach the age of a certain stage of chronological development. Sampling in this study using total sampling was done by taking samples or respondents who happened to be in Di Samanhudi Estate Village, South Binjai District. as many as 30 people. In this paper the author uses questionnaire / questionnaire data collection with Guttman scale. The results of the study from 30 respondents aged 60-65 years as many as 12 people (40%), 66-70 years as many as 10 people (33%), 71-75 years as many as 8 people (27%), from 30 respondents with elementary education as 16 people (53%), SMP as many as 7 people (23%), SMA as many as 5 people (17%), colleges as many as 2 people (7%), from 30 respondents the factors that cause insomnia based on psychological factors as many as 12 people (40% ) based on psychiatric problems as many as 2 people (7%) based on physical illness as many as 3 people (10%) based on environmental factors as many as 2 people (7%) based on lifestyle of 2 people (7%) based on excessive napping of 9 people (30 %). It is hoped that the elderly will develop the habit of sleeping at night and try to reduce stress and depression, exercise or exercise every day to create a healthy body and soul, not smoke and drink alcohol, or coffee at night, regular health checks especially near the nearest health, hopefully it can reduce and lower the rate of increase in insomnia in the elderly.Keywords: Factors that affect insomnia in the elderly